Four-layer radioimmunoassay for detection of adenovirus in stool. - Halonen, P (1980)
A four-layer antispecies radioimmunoassay (RIA) was developed for the detection of adenovirus in stool specimens. Polystyrene beads were used as the solid phase, anti-adenovirus guinea pig immunoglobulin (1 microgram per bead) was used as the primary antibody, anti-adenovirus rabbit immunoglobulin (16 micrograms/ml) was used as the secondary antibody, and 125I-labeled sheep anti-rabbit immunoglobulin was used as the indicator antibody. A highly purified, crystallized adenovirus type 2 hexon antigen was used as the immunizing antigen for the production of hyperimmune sera. The sensitivity of the test was 1 ng of hexon protein per ml. Each of the 13 stool specimens positive for adenovirus by electron microscopy was positive for adenovirus by the RIA. Of 200 nonconcentrated stool specimens negative by electron microscopy, 14 additional specimens were positive by the RIA, increasing the detection rate from 6% by electron microscopy to 13% by the RIA. A confirmatory test was done on the RIA-positive, electron microscopy-negative specimens, and the test indicated a true specific result with each specimen. A confirmatory test was also done on each specimen with a low positive counts per minute value. The specificity of the RIA was further demonstrated by the fact that a positive result was found with only 3 of 295 specimens positive by the rotavirus RIA. In two of these three specimens, adenovirus and rotavirus were also detected simultaneously by electron microscopy, and the third specimen was from a patient with serological evidence for a dual infection. The adenovirus and rotavirus RIAs are now in a routine diagnostic laboratory, and in the 307 stool specimens tested during the first 5 months, the positive rate was 32% for rotavirus and 9.5% for adenovirus.